إسهامات المكتبات الإلكترونية في إنجاز الدراسات العلمية لدى أساتذة قسم الإعلام والإتصال بجامعة الأغواط - عبد الرحمان ديدي; فائزة سويسي; د/أسامة مروقي (جامعة عمار ثليجي الاغواط, 2023)
ملخص الدراسة باللغة العربية هدفت دراستنا الحالية إلى : تسليط الضوء على المكتبات الإلكترونية، ومحاولة معرفة مدى إسهامات المكتبات الإلكترونية في إنجاز الدراسات سواء المساهمة في إنجاز أطروحة الدكتوراه أو في إنجاز المقالات العلمية . و قد تم الإعتمادعلى المنهج المنهج الوصفي التحليلي حيث يعتبر أسلوب من أساليب التحليل المرتكز على معلومات كافية ودقيقة عن ظاهرة أو موضوع محدد من خلال فترات زمنية معلومة وذلك من أجل الحصول على نتائج عملية تم تفسيرها بطريقة موضوعية،وبما ينسجم مع المعطيات الفعلية للظاهرة ، أما أداة الدراسة فتمثلت في الإستمارة وتم توزيع 24 إستمارة على عينة الدراسة. وتمثل مجتمع البحث ( عينة الدراسة ) الذي نقوم بدراسته في أساتذة قسم الإعلام والإتصال بجامعة الأغواط، وإنطلاقا مما سبق قمنا بإختيار العينة القصدية. وتوصلت نتائج دراستنا إلى أن : - المكتبات الإلكترونية تساهم في إنجاز الدراسات العلمية لدى أساتذة قسم الإعلام والإتصال بجامعة الأغواط. - تساهم المكتبات الإلكترونية في إنجاز أطروحة الدكتوراه لدى أساتذة قسم الإعلام والإتصال بجامعة الأغواط. - تساهم المكتبات الإلكترونية في إنجاز المقالات العلمية لدى أساتذة قسم الإعلام والإتصال بجامعة الأغواط. Study summary Our current study aimed at: shedding light on electronic libraries, and trying to find out the extent to which electronic libraries contribute to the completion of studies, whether contributing to the completion of a doctoral dissertation or the completion of scientific articles. The descriptive analytical approach was relied upon, as it is considered a method of analysis based on sufficient and accurate information on a specific phenomenon or topic through known time periods, in order to obtain practical results that were interpreted in an objective manner, and in a manner consistent with the actual data of the phenomenon. The study was represented in the questionnaire, and 24 questionnaires were distributed to the study sample. The research community (the study sample) that we are studying is represented by the professors of the Department of Media and Communication at the University of Laghouat, and based on the foregoing, we chose the intended sample. The results of our study concluded the following: - Electronic libraries contribute to completing the scientific studies of the professors of the Department of Information and Communication at the University of Laghouat. - Electronic libraries contribute to the completion of the doctoral dissertation of the professors of the Department of Information and Communication at the University of Laghouat. - Electronic libraries contribute to the completion of scientific articles for professors of the Department of Information and Communication at the University of Laghouat.